Stress in the workplace the contrasting effects of 10 minutes of listening to Chopin vs. HRV biofeedback on autonomic reactivity and cognitive performance - Smit, Sita (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Includes abstract. Includes bibliographical references.